Earthquake Analysis Using the Probabilistic Seismic Hazard Analysis (PSHA) Method in Palu City - Harsano Jayadi; Icha Untari Meidji; Irna Hidayat; Abdullah (Faraday: Journal of Fundamental Physics, Research, and Applied Science, 2025)
Palu, Indonesia, is a region with high seismic activity due to its location on the active Palu-Koro fault line. This study aims to analyze the probability of earthquakes, the spatial and temporal distribution of earthquake occurrences, and disaster mitigation efforts in anticipation of earthquakes in the region. Earthquake data in Palu City were analyzed based on magnitude, depth, and frequency of occurrence. The results indicate that most earthquakes occur at shallow depths ranging from approximately 10 to 56.8 kilometers, with a dominance of moderate magnitude (5.0–5.7 M_w). Over the past two decades, there has been an increase in the temporal occurrence of earthquakes, with a significant surge in 2018 when a magnitude 7.5 earthquake triggered a tsunami and liquefaction. Probability analysis indicates that earthquakes with high seismicity indices are highly likely to occur within a 10- to 50-year timeframe. The spatial distribution reveals that earthquakes tend to be concentrated around the Palu-Koro fault, the primary source of seismic activity in the region. These findings provide important insights into the seismic patterns of Palu City and can inform community preparedness and disaster mitigation strategy development.